Ge=B π‐Bonding: Synthesis and Reversible [2+2] Cycloaddition of Germaborenes. Issue 8 (7th January 2020) - Raiser, Dominik; Sindlinger, Christian P.; Schubert, Hartmut; Wesemann, Lars
Abstract: Phosphine‐stabilized germaborenes featuring an unprecedented Ge=B double bond with short B⋅⋅⋅Ge contacts of 1.886(2) (4 ) and 1.895(3) Å (5 ) were synthesized starting from an intramolecular germylene–phosphine Lewis pair (1 ). After oxidative addition of boron trihalides BX3 (X=Cl, Br), the addition products were reduced with magnesium and catalytic amounts of anthracene to give the borylene derivatives in yields of 78 % (4 ) and 57 % (5 ). These halide‐substituted germaborenes were characterized by single‐crystal structure analysis, and the electronic structures were studied by quantum‐chemical calculations. According to an NBO NRT analysis, the dominating Lewis structure contains a Ge=B double bond. The germaborenes undergo a reversible, photochemically initiated [2+2] cycloaddition with the phenyl moiety of a terphenyl substituent at room temperature, forming a complex heterocyclic structure with Ge IV in a strongly distorted coordination environment. Abstract : Germaborenes with the first authentic Ge=B double bond were synthesized. Upon photoactivation, germaborenes undergo a reversible [2+2] cycloaddition reaction with an arene moiety.